Adherence to Surgical Care Improvement Project measures: the whole is greater than the parts. (December 2010) - Dellinger, E Patchen
Evaluation of: Stulberg JJ, Delaney CP, Neuhauser DV, Aron DC, Pingfu F, Koroukian SN: Adherence to surgical care improvement project measures and the association with postoperative infections. JAMA 303, 2497–2485 (2010); and, Hawn T: Surgical care improvement – should performance measures have performance measures. JAMA 303, 2527–2528 (2010). Much effort has been put into the Surgical Care Improvement Project (SCIP) in an effort to reduce surgical complications with a significant emphasis on reducing the rate of surgical site infections. The causes and the prevention of surgical site infections are complex and multifactorial. By the nature of its size and scope, SCIP is naturally somewhat oversimplified and incomplete. Nevertheless, all the measures are supported by strong prospective evidence. Stulberg et al. examine the association between adherence to SCIP infection measures and the occurrence of surgical site infections in a large administrative database and conclude that while the individual measures for the most part do not appear to be associated with a lower surgical site infection risk, the performance of all relevant measures does.